INCLUSIVE EDUCATION IN THE FIELD OF PHYSICAL EDUCATION AND SPORTS - Magomedov, Ruslan; Popova, Marianna; Vartanova, Yana (Revista Inclusiones, 2019)
The article considers the theoretical and practical aspects of the study of inclusive education in the field of physical education and sports. The model of logic of forming readiness of future physical education teachers for inclusive education is graphically presented on the example of senior preschoolers, which indicates inputs, outputs, directions, and mechanisms of managerial and pedagogical effects of social order parameters from the state and the society. The expediency of introducing the model into the educational process of the university has been experimentally proved.